Development and definition of a simplified scanning procedure and scoring method for Haemophilia Early Arthropathy Detection with Ultrasound (HEAD-US) - Martinoli, Carlo; Alberighi, Ornella Della Casa; Di Minno, Giovanni; Graziano, Ermelinda; Molinari, Angelo Claudio; Pasta, Gianluigi; Russo, Giuseppe; Santagostino, Elena; Tagliaferri, Annarita; Tagliafico, Alberto; Morfini, Massimo (Thrombosis and Haemostasis, 2013)
The aim of this study was to develop a simplified ultrasound scanning procedure and scoring method, named Haemophilia Early Arthropathy Detection with UltraSound [HEAD-US], to evaluate joints of patients with haemophilic arthropathy. After an initial consensus-based process involving a multidisciplinary panel of experts, three comprehensive and evidence-based US scanning procedures to image the elbow, knee and ankle were established with the aim to increase sensitivity in detection of early signs of joint involvement while keeping the technique easy and quick to perform. Each procedure included systematic evaluation of synovial recesses and selection of a single osteochondral surface for damage analysis. Based on expert consensus, a simplified scoring system based on an additive scale was created to define the joint status and, in perspective, to offer a tool to evaluate disease progression and monitor the result of treatment in follow-up studies.
Keywords: Haemophilic arthropathy; joints; scoring systems; ultrasonography; synovitis; osteochondral damage